Rancang Bangun Sistem Informasi Pemesanan Paket Makanan Catering - Alhamidi, Alhamidi; Asmara, Rini; Iswandy, Eka (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
In a world of information technology nowadays, time plays an important role. In connection with the increasing the community needs for time, people continue to try to find something new, something that can be used to do many things quickly and efficiently, especially in the field of data and information processing. Catering is a business that serves quality food for customers at various events. Currently, data on catering orders and transactions still has many deficiencies, including the order list that still using manually by written on the book, sales still use purchase invoices in the form of receipts and using ledgers to make a report generation, causing data to be inaccurate and duplicated data. This research produces an information system for ordering catering food packages that will help the caterers manage transaction data and prepare reports on catering food packages.